Pengaruh Return on Asset terhadap Nilai Perusahaan dengan Struktur Modal sebagai Variabel Moderasi pada Perusahaan Manufaktur Sub Sektor Industri Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2015-2022 - Zachari Abdallah; Rika Desiyanti (Syntax Literate, 2023)
The study aims to find out is there any influence of Return On asset On Firm Value with Capital Structure as a moderating variable in Manufacturing Sub Sector Food and Beverage Industry Needs registered in Indonesia Stock Exchange (BEI) in 2015-2022. Data used in study this secondary data from report annual companies listed on the Indonesia Stock Exchange (BEI) for the period 2015-2022. As for the sample obtained is as many as 30 samples with use method purposive sampling. Based on the results of the study indicate that: There is influence between the Return On Asset on Firm Value seen at (10,233 > 2,006) with a significant value <0,05 (0,000 < 0,050). There is effect of Return on Asset and Capital Structure on Firm Value where seen at (7,450 > 3,172). Capital Structure is not proven as a moderating variable between the return on asset and the Firm Value Whose a significant value (0,201 > 0,050). There R Square determination coeeficient of influence of the Return on Asset on Firm Value moderated by Capital Structure is 21,9 or 22%.